The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1172/jci.insight.157433
|View full text |Cite
|
Sign up to set email alerts
|

Role of the caspase-8/RIPK3 axis in Alzheimer’s disease pathogenesis and Aβ-induced NLRP3 inflammasome activation

Abstract: The molecular mediators of cell death and inflammation in Alzheimer's disease (AD) have yet to be fully elucidated. Caspase-8 is a critical regulator of several cell death and inflammatory pathways; however, its role in AD pathogenesis has not yet been examined in detail. In the absence of Caspase-8, mice are embryonic lethal due to excessive RIPK3-dependent necroptosis. Compound RIPK3 and Caspase-8 mutants rescue embryonic lethality, which we leveraged to examine the roles of these pathways in an amyloid beta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 75 publications
1
12
0
Order By: Relevance
“…However, it is important to note that we have not been able to detect appreciable levels of microglia cell death by TUNEL (terminal deoxynucleotidyl transferase dUTP nick end labeling) staining in the 5xFAD model in our previous studies. 27,35 Therefore, it is more likely that enhanced microglial proliferation contributes to the increase in microglia numbers seen in SHIP-1-deficeint 5xFAD mice.…”
Section: Ship-1 Deletion Increases Microglial Numbers and Mobilizatio...mentioning
confidence: 99%
“…However, it is important to note that we have not been able to detect appreciable levels of microglia cell death by TUNEL (terminal deoxynucleotidyl transferase dUTP nick end labeling) staining in the 5xFAD model in our previous studies. 27,35 Therefore, it is more likely that enhanced microglial proliferation contributes to the increase in microglia numbers seen in SHIP-1-deficeint 5xFAD mice.…”
Section: Ship-1 Deletion Increases Microglial Numbers and Mobilizatio...mentioning
confidence: 99%
“…Pycard (PYD and CARD domain containing gene, encoding for adapter protein apoptosis-associated speck-like protein containing a CARD (ASC)) codes for an inflammasome component and is involved in regulation of autophagy. Previous reports demonstrated that released ASC specks can bind to Aβ, enhance its aggregation, and increase its toxicity [ 159 ]. In our study, Pycard turned out to be a unique fingerprint for the RS cortex of female APP/PS1 mice.…”
Section: Discussionmentioning
confidence: 99%
“…However, when caspase-8 was inhibited genetically or chemically, the peroxisome (RIPK3–MLKL) could bind to the NLRP3 inflammasome to promote IL-1β activation, which is consistent with other previous studies demonstrating that both pathways are intracellular in origin. These findings indicate that RIPK3-induced inflammation may be driven by factors other than necroptosis and DAMP release [ 72 , 73 ].
Fig.
…”
Section: Non-necrotic Function Of Ripk3mentioning
confidence: 99%